Complete occlusive dressing for hypospadias in children - Khan, Tanvir Roshan; Singh, Shrikesh; Prakash, Divya (International Surgery Journal, 2021)
Background: Dressing after hypospadias repair is particularly important to provide adequate pressure, hemostasis and prevent edema. Ideal dressing remains a challenge and multiple methods of dressings after hypospadias repair have been reported. Not many types of dressings are described in children and it varies from places and institutes. Present study describes the method of application of complete occlusive dressing in the children undergoing hypospadias repair. Methods: It is a prospective analysis of the operated patients of hypospadias who were offered complete occlusive dressing of the penis following surgery in a tertiary teaching hospital. The outcome was assessed on the basis of cosmetic and functional appearance after removal of the dressing namely, edema, ischemia, fistula formation if any Results: A total of 100 patients were operated during the study period of two years. The age ranged from 1 year to 16 years. All patients were provided complete occlusive dressing of the penis following surgery (urethroplasty). The patients tolerated the dressing very well with minimal postoperative edema with good functional and cosmetic outcome. There were some minor complications associated with this type of dressing. Conclusions: The complete occlusive dressing in the hypospadias surgery is an alternative type of dressing in children after hypospadias surgery. The dressing is easily available, and the method can be easily learned and reproduced. There is no need for repeated changes or pain on removal, the patients are comfortable with the dressing and it keeps them mobile. It is helpful in reducing the postoperative edema and subsequent complications.